Steinernema poinari sp. n. (Nematoda: Steinernematidae) a new entomopathogenic nematode from the Czech Republic - Mráček, Zdeněk; Nermuť, Jiří (Zootaxa, 2014)
A new steinernematid nematode, herein described as Steinernema poinari sp. n., was recovered by baiting soil samples with the last instar wax moth larvae Galleria mellonella in three localities of southwest Bohemia, Czech Republic. Morphological and molecular data confirmed this nematode as a new species which belongs to the affine/intermedium group. S. poinari sp. n. was characterized by male, female and infective juvenile morphological observations. Male spicules are robust with a pointed tip, SW% = 109 (98-123) and GS% = 70 (58-87). The tail terminus of the first generation have a papillated mucron, whereas in the second generation a short filamentous mucron sometimes develops. Females of the first generation have a moderately protruding vulva, postanal swelling absent or slightly developed. Second generation females have a long filamentous mucron on the tail tip. Infective juvenile have a body length of 768 µm, lateral field formula 2, 5, 6, 5, 2, 1, ratio D% of 46 (40-55), E% of 84 (76-95) and H% of 50 (43-56). The new species was characterized by sequences of ITS and D2D3 regions of ribosomal DNA. S. poinari sp. n. can also be separated from S. affine and S. intermedium by cross-breeding tests.
Keywords: Česká republika; hlístice; Phylogeny; Czech Republic; Insecta; DNA, Ribosomal Spacer; Male; fylogeneze; Animals; Female; mužské pohlaví; ženské pohlaví; Nematoda; hmyz; zvířata; mezerníky ribozomální DNA